2012
DOI: 10.1590/s0100-83582012000200024
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance indices as a diagnostic tool for weed control performed by multipurpose equipment in precision agriculture

Abstract: Several tools of precision agriculture have been developed for specific uses. However, this specificity may hinder the implementation of precision agriculture due to an increasing in costs and operational complexity. The use of vegetation index sensors which are traditionally developed for crop fertilization, for site-specific weed management can provide multiple utilizations of these sensors and result in the optimization of precision agriculture. The aim of this study was to evaluate the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
(45 reference statements)
1
5
0
6
Order By: Relevance
“…The technique was effective; however, it becomes more time consuming with the increasing complexity of the spatial distribution of weeds in the area. Recently, with the use of optical sensors in Brazilian agriculture, some studies have shown promising results for use in weed mapping (Silva Jr. et al, 2012;Merotto Jr. et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique was effective; however, it becomes more time consuming with the increasing complexity of the spatial distribution of weeds in the area. Recently, with the use of optical sensors in Brazilian agriculture, some studies have shown promising results for use in weed mapping (Silva Jr. et al, 2012;Merotto Jr. et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…As for the automatic collection of data, one can use color cameras and infrared coupled to a land (Silva Jr. et al, 2012) or air equipment (Candón et al, 2012b) and sensors and vegetation index (Chang et al, 2004;Merotto Jr. et al, 2012). On the other hand, in the conventional sampling meshes are commonly used sample, dividing the area into smaller squares, where the georeferenced samples of the weed are held (Merotto Jr. & Bredemeier, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Как уже указывалось выше, СОС сорняков статистически значимо (при р  0,05) отличается от СОС пшеницы. Наибольшие различия наблюдаются в ИК и зеленой области спектра вследствие того, что сорная растительность имеет более зеленый цвет, чем листья пшеницы (особенно в начале послезимней вегетации и после прохождения максимума вегетации), что подтверждает данные, полученные исследователями ранее (19,34). Меньшие, но в некоторых случаях достаточно заметные различия наблюдаются в красной области спектра, где сорная растительность немного сильнее отражает солнечную энергию в сравнении с листьями пшеницы из-за несколько большего содержания в ней влаги (35).…”
Section: рис 1 примеры кривых спектрального отражения листьев озимоunclassified
“…Esses índices podem ser utilizados, como referência, na adubação das culturas e no manejo de p lantas daninhas (MEROTTO et al, 2012).…”
unclassified